Recent Progress of BODIPY Dyes With Aggregation-Induced Emission - Liu, Zhipeng; Jiang, Zhiyong; Yan, Ming; Wang, Xiaoqing (Frontiers in Chemistry, 2019)
With the development of organic optoelectronic materials and bioimaging technology, to exploit organic luminescent materials with high luminescent efficiency in aggregation-state has become a research hotspot. BODIPYs have become one of the research objects of this kind of materials because of their obvious advantages. This review focuses on the design and synthesis of AIE-type BODIPYs, the mechanism of AIE properties and their applications in recent years. Through classification, analysis, and summary, this review aims to explore the structure-activity relationship of AIE-type BODIPYs, and to provide ideas for the further design and potential applications of AIE-active fluorescent materials.